Maxillofacial Fibrous Osteodystrophy in Equine: Case Report - Ospina, Juan C.; Doncel, Benjamín; García, Noel Verjan (Brazilian Journal of Veterinary Pathology, 2014)
A 14 year-old pregnant mare developed poor body condition (2/5) and diarrhea while grazing in kikuyu grass (Pennisetum clandestinum). Clinical findings included bulging of nasal and maxillary bones and mouth lacerations associated to spicules on the surface of molars and premolars. Teeth were easily fragmented and fell off. Necropsy findings included severe softening of the maxillary and mandibular bones. The mandible was easily breakable near to the masseter´s fossa. The parathyroid gland was increased in size. Histological findings were characterized by multiple irregular and very thin bone spicules in the bone tissue, most of them with microfractures, severe osteoclasts-mediated bone resorption and fibrous connective tissue proliferation. Hyperplasia and hypertrophy of parathyroid chief cells with cytoplasmic vacuolization were also observed. In conclusion, maxillofacial fibrous osteodystrophy caused by nutritional secondary hyperparathyroidism developed in a pregnant mare while grazing kikuyu grass for long periods of time without appropriate supplements. Kikuyu grass is characterized by high levels of oxalic acid that forms insoluble oxalates responsible for low calcium absorption in the small intestine and the progress of hyperparathyroidism.